Cenani-Lenz syndactyly in siblings with a novel homozygous LRP4 mutation and recurrent hypoglycaemia. Issue 2 (April 2020) - Steel, Edward; Hurst, Jane A; Cullup, Thomas; Calder, Alistair; Sivakumar, Branavan; Shah, Pratik; Wilson, Louise C
Abstract : Cenani-Lenz syndactyly (CLS) is a rare autosomal recessive syndrome characterized by disorganized oligosyndactyly of upper and lower limbs as well as radioulnar synostosis. Structural renal abnormalities are also common. We report two affected brothers, born to orthodox Jewish parents, in whom we found a novel homozygous missense variant c.4910G>A; p.(Cys1637Tyr) in LRP4 situated in an EGF-like domain between the fourth beta-propeller and transmembrane domains. Both brothers have had recurrent ketotic hypoglycaemia which has not been associated previously. We present 3D computed tomographic imaging illustrating the limb abnormalities in detail.